2002
DOI: 10.1046/j.1365-2354.2002.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of complementary therapies among breast and prostate cancer patients in Finland

Abstract: This study describes the use of complementary therapies (CTs) among breast (women) and prostate cancer patients (men) in Finland. The data were collected using a self-administered postal questionnaire. Responses were received from 216 women (response rate 54.9%) and 190 men (response rate 55.4%). Data analysis was based on descriptive statistics, the chi-square test and Fisher and Wilcoxon tests. Interpretation of the responses to the open-ended questions used the method of content analysis. Half the responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
3
24
0
Order By: Relevance
“…Previous studies have reported, among survivors of various cancers, CAM use rates of 53% (Miller et al, 1998), 83.3% (Richardson et al, 2000), and 21.9% (Begbie et al, 1996); for breast cancer, CAM use rates of 28.1% (Burnstein, Gelber, Guadagnoli, & Weeks, 1999); for prostate cancer, CAM use rates of 37% (Hall, Bissonette, & Theodorescu, 2003); and for a study of breast and prostate cancer survivors, CAM use rates of 30% (Salmenpera, 2002). In this group of cancer survivors, CAM use was common.…”
Section: Discussionmentioning
confidence: 69%
“…Previous studies have reported, among survivors of various cancers, CAM use rates of 53% (Miller et al, 1998), 83.3% (Richardson et al, 2000), and 21.9% (Begbie et al, 1996); for breast cancer, CAM use rates of 28.1% (Burnstein, Gelber, Guadagnoli, & Weeks, 1999); for prostate cancer, CAM use rates of 37% (Hall, Bissonette, & Theodorescu, 2003); and for a study of breast and prostate cancer survivors, CAM use rates of 30% (Salmenpera, 2002). In this group of cancer survivors, CAM use was common.…”
Section: Discussionmentioning
confidence: 69%
“…Of note in this research is that those CAM therapies most commonly used by cancer patients are those same therapies that are most commonly discussed in the Canadian print media [1,2,11,15,18], suggesting a potential relationship between media information and CAM decision-making. Similarly, the observed trend in reporting frequency parallels the trend in CAM use, which began to increase in the early 1990s and which seems to have leveled off over Fig.…”
Section: Discussionmentioning
confidence: 82%
“…Examples of such therapies commonly used by cancer patients are mind-body approaches, such as meditation or prayer, and biologically based therapies, such as herbs, vitamins, supplements, and special diets [1,2,11,15,18]. When these same therapies are used in place of conventional medicine, they are referred to as alternative therapies.…”
Section: Introductionmentioning
confidence: 99%
“…In studies published after 2000, the rates of CAM use range from 28% of prostate cancer patients in Finland [6] to 91% of radiotherapy or chemotherapy patients in the United States [7], where CAM is chiefly complementary [1].…”
Section: Introductionmentioning
confidence: 99%